EL HARAKAH : Al-Khattu Al-'Arabiyyi Wa Juhudu Al-Myslimina Fi Al-Muhafadzati 'Alaihi - Syuhadak (UIN Maulana Malik Ibrahim, 2016)
it cannot be denied that beauty of calligraphy is an excellence correlated to its writer that will raise his/her ability higher than other.